2017
DOI: 10.1097/j.pain.0000000000000831
|View full text |Cite
|
Sign up to set email alerts
|

The role of calcitonin gene–related peptide in peripheral and central pain mechanisms including migraine

Abstract: Calcitonin gene–related peptide (CGRP) is a 37-amino acid peptide found primarily in the C and Aδ sensory fibers arising from the dorsal root and trigeminal ganglia, as well as the central nervous system. Calcitonin gene–related peptide was found to play important roles in cardiovascular, digestive, and sensory functions. Although the vasodilatory properties of CGRP are well documented, its somatosensory function regarding modulation of neuronal sensitization and of enhanced pain has received considerable atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
404
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 446 publications
(420 citation statements)
references
References 205 publications
(493 reference statements)
12
404
0
4
Order By: Relevance
“…The protein most associated with sensitization and activation of primary and secondary trigeminal neurons, and hence, the underlying pathology of migraine, is the neuropeptide CGRP (Bigal et al, 2013; Iyengar et al, 2017). CGRP is proposed to play a fundamental role in migraine since cerebrospinal fluid levels of CGRP are elevated during and between migraine attacks (van Dongen et al, 2017) and CGRP levels correlate with treatment response to anti-migraine drugs (Karsan and Goadsby, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein most associated with sensitization and activation of primary and secondary trigeminal neurons, and hence, the underlying pathology of migraine, is the neuropeptide CGRP (Bigal et al, 2013; Iyengar et al, 2017). CGRP is proposed to play a fundamental role in migraine since cerebrospinal fluid levels of CGRP are elevated during and between migraine attacks (van Dongen et al, 2017) and CGRP levels correlate with treatment response to anti-migraine drugs (Karsan and Goadsby, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, members of the mitogen-activated protein kinase (MAPK) family mediate intracellular signaling cascades that promote neuron-glia interactions and maintain a hyperexcitable state of nociceptive neurons (Crown, 2012; Ji et al, 2009; Ji et al, 2013). The neuropeptide calcitonin gene-related peptide (CGRP), whose expression is regulated by MAPK and is strongly implicated in migraine pathology, can promote sensitization of primary and secondary trigeminal nociceptive neurons and activation of satellite glial cells in the ganglion and astrocytes and microglia in the spinal cord (Durham, 2016; Iyengar et al, 2017; Seybold, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that CGRP is neurogenic and is released from motor nerve terminals in different tissues (Uchida et al., 1990; Sakaguchi et al., 1991; Macdonald et al., 2008; Iyengar et al. 2017). Thus, it looks more likely that ryanodine application to motor synapses initiates calcium release from presynaptic Ca 2+ ‐stores leading to secretion of endogenous CGRP from motor nerve terminals followed by an increase in MEPPs amplitude in motor synapses.…”
Section: Discussionmentioning
confidence: 99%
“…21 CGRP is a 37-amino acid neuropeptide, first described in 1983. [26][27][28][29][30] About 50% of the neurons in the trigeminal ganglion is CGRP-immunoreactive. 22 Neuropeptides are proteinaceous substances that are synthesized in the nucleus of the neuron and released from dense core vesicles.…”
Section: Medications Targeting Cgrpmentioning
confidence: 99%